Expanded HIV testing coverage is associated with decreases in late HIV diagnoses. (17th July 2015) - Ransome, Yusuf; Terzian, Arpi; Addison, Diane; Braunstein, Sarah; Myers, Julie; Abraham, Bisrat; Nash, Denis
Abstract : Objective: Expanded HIV testing coverage could result in earlier diagnosis of HIV, along with reduced morbidity, mortality and onward HIV transmission. Design: Longitudinal analysis of aggregate, population-based surveillance data within New York City (NYC) ZIP codes. Methods: We examined new HIV diagnoses and recent HIV testing to examine whether changes in recent HIV testing coverage (last 12 months) were associated with changes in late HIV diagnosis rates within NYC ZIP codes during 2003–2010, a period of expansion of HIV testing in NYC. Results: Overall, recent HIV testing coverage increased from 23 to 31% during 2003–2010, while the rate of late HIV diagnoses decreased from 14.9 per 100 000 to 10.6 per 100 000 population. Within ZIP codes, each 10% absolute increase in recent HIV testing coverage was associated with a 2.5 per 100 000 absolute decrease in the late HIV diagnosis rate. ZIP codes with the largest changes in HIV testing coverage among men were more likely to have the largest (top quartile) declines in late HIV diagnosis rates among men [adjusted odds ratio (aOR)men  = 4.0; 95% confidence interval (95% CI) 1.5–10.8], compared with ZIP codes with no or small changes in HIV testing coverage. This association was not significant for women (aORwomen  = 1.4; 95% CI 0.50–4.3). Significant geographic disparities in late HIV diagnosis rates persisted in 2009/2010. Conclusion: Increases in recent HIV testing coverage may have reduced late HIV diagnoses among men. Persistent geographic disparities underscore the need for continued expansion of HIV testing to promote earlier HIV diagnosis.